Proteomic Analysis of Differentially Accumulated Proteins in Cucumber (Cucumis sativus) Fruit Peel in Response to Pre-storage Cold Acclimation - Wang, Bin; Shen, Fei; Zhu, Shijiang (Frontiers in Plant Science, 2018)
Harvested fruit are still living organs and respond to environmental stimuli. Low temperature storage is effective in extending life of harvested fruit, but it may also cause chilling injury. Cold acclimation has been shown to induce chilling tolerance in plants, but what proteomic changes caused by cold acclimation are related to defense against chilling stress remains largely unclear. Here, 3 d of pre-storage cold acclimation (PsCA) at 10oC reduced chilling injury and secondary disease severity in cucumber stored at 5oC by 51% and 94%, respectively, compared with the control which was directly stored at 5oC. Proteomic analysis of cucumber peel identified 21 significant differentially-accumulated proteins (SDAPs) right after PsCA treatment and 23 after the following cold storage (PsCA+CS). These proteins are mainly related to stress response and defense (SRD), energy metabolism, protein metabolism, signal transduction, primary metabolism and transcription. The SRD proteins, which made up 37% of the 21 and 47% of the 23, respectively, represented the largest class of SDAPs, and all but one protein were up-regulated, suggesting accumulation of proteins involved in defense response is central feature of proteomic profile changes brought about by PsCA. In fruit just after PsCA treatment, the identified SDAPs are related to responses to various stresses, including chilling, salt stress, dehydration, fungi, bacteria, insects, and DNA damage. However, after prolonged cold storage, the targeted proteins in acclimated fruit were narrowed down in scope to those involved in defense against chilling and pathogens. The change patterns at the transcription level of the majority of the up-regulated differentially-accumulated proteins were highly consistent with those at protein level. Taken all, the results suggest that the short-time cold acclimation initiated comprehensive defense responses in cucumber fruit at first, while the long term storage thereafter altered the responses more specifically to chilling. These findings add to the understanding of plants’ molecular responses to cold acclimation.